A Diverse Repertoire of Human Immunoglobulin Variable Genes in a Chicken B Cell Line is Generated by Both Gene Conversion and Somatic Hypermutation - Leighton, Philip A.; Schusser, Benjamin; Yi, Henry; Glanville, Jacob; Harriman, William (Frontiers in Immunology, 2015)
Chicken immune responses to human proteins are often more robust than rodent responses because of the phylogenetic relationship between the different species. For discovery of a diverse panel of unique therapeutic antibody candidates, chickens therefore represent an attractive host for human-derived targets. Recent advances in monoclonal antibody technology, specifically new methods for the molecular cloning of antibody genes directly from primary B cells, has ushered in a new era of generating monoclonal antibodies from non-traditional host animals that were previously inaccessible through hybridoma technology. However, such monoclonals still require post-discovery humanization in order to be developed as therapeutics. To obviate the need for humanization, a modified strain of chickens could be engineered to express a human sequence immunoglobulin variable region repertoire. Here, human variable genes introduced into the chicken immunoglobulin loci through gene targeting were evaluated for their ability to be recognized and diversified by the native chicken recombination machinery that is present in the B-lineage cell line DT40. After expansion in culture the DT40 population accumulated genetic mutants that were detected via deep sequencing. Bioinformatic analysis revealed that the human targeted constructs are performing as expected in the cell culture system, and provide a measure of confidence that they will be functional in transgenic animals.